Guns of the vigilantes - Johnstone, William W.; Johnstone, J. A. (Pinnacle Books, Kensington Publishing Corp., 2024)
After seeing an entire family murdered, and with the eldest daughter missing, young deputy Dan Caine throws away his badge, forms a vigilante team and goes after the killers because come hell or high water, justice will be served.